Demographic dimensions of resilient farming systems in the EU - Alfons Balmann; Erwin Wauters; Franziska Appel; Jo Bijttebier; Isabeau Coopmans; Christine Pitson (Resilient and sustainable farming systems in Europe: Exploring diversity and pathways, 2022)
Demographic trends affect EU farms' availability of successors and hired labour. If a potential successor is available, generational renewal on family farms occurs in stages: the successor's identity formation, the farm transfer, and the farm development. If generational renewal on the farm level is not possible, adaptations of other farms can ensure the future provision of private and public goods on the regional level if there is a sufficient supply of hired labour.
Keywords: 330; demographics; farm succession; structural change; resilience; farming systems; Common Agricultural Policy